2014
DOI: 10.1038/cdd.2014.132
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tissue-specific stem cells by reprogramming factors, and tissue-specific selection

Abstract: Although induced pluripotent stem (iPS) cells have significant implications for overcoming most of the ethical issues associated with embryonic stem (ES) cells, there are still several unresolved issues related to the use of iPS cells for clinical applications, such as teratoma formation. In this study, we were able to generate tissue-specific stem (induced tissue-specific stem; iTS) cells from the pancreas (iTS-P) or liver (iTS-L) by transient overexpression of reprogramming factors, combined with tissue-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 38 publications
6
43
0
Order By: Relevance
“…A recent report has shown that transient expression of the reprogramming factors is able to generate tissue-specific stem cells from pancreatic cells and liver cells (55) …”
Section: Discussionmentioning
confidence: 99%
“…A recent report has shown that transient expression of the reprogramming factors is able to generate tissue-specific stem cells from pancreatic cells and liver cells (55) …”
Section: Discussionmentioning
confidence: 99%
“…Cells or cell clumps isolated from a normal pancreas, or those in vitro-produced as a result of transdifferentiation through forced expression of exogenous pancreas/duodenum homeobox protein 1 (Pdx1), Neurogenin-3 (Ngn3), and V-maf musculoaponeurotic fibrosarcoma oncogene homolog A (Mafa) in acinar cells [7] are suitable donors for IPPCT. Tissue-specific stem cells obtained by reprogramming of normal [8] or NOD [9] mouse-derived pancreatic cells, all of which have a potential to produce insulin, would also be suitable donors for IPPCT. Elevated serum levels of insulin, decreased fasting blood glucose levels and recovery of healthy islets in those IDDM model animals may be good indicators of recovery from hyperglycemia associated with IDDM.…”
Section: Experimental Example-2: In Vivo Functional Analysis Of Cellsmentioning
confidence: 99%
“…We place such importance on cell adhesion because many molecular biological techniques for cells are performed under cell adhesion conditions. Regenerative medicine associated with the establishment of pluripotent stem cells [9][10][11][12] and gene therapy [13][14][15] may offer new treatments for severe pancreatic diseases, such as diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…16 It is also difficult to establish pancreatic human induced pluripotent stem cells (iPSCs) and iPSC-like cells. 9,10 Developmentally, both exocrine tissue and pancreatic islets are differentiated from pancreatic buds. Recently, exocrine tissue has been reported to be essential for inducing the differentiation of pancreatic islets.…”
Section: Introductionmentioning
confidence: 99%